ICOS ATC CO Release from Norunda (32.0 m) - Irene Lehner; Meelis Molder (Integrated Carbon Observation System, 2025)
Quality-controlled data on molar fraction of atmospheric CO
Instrument Id 462: H2O correction updated. An interpolation over time of the water vapor correction factors has been applied up to 2022-02-02 and then between 2022-03-21 and 2024-02-28
Lehner, I., Molder, M. (2025). ICOS ATC CO Release from Norunda (32.0 m), 2017-04-01–2025-03-31, ICOS RI, https://hdl.handle.net/11676/nutMQwtu6Rn-GMekLsOgfypV
Keywords: Atmosphere Thematic Centre; CO; ICOS; dry air mole fraction; time instant, UTC; time instant, UTC; quality flag; quality flag; number of points; number of points; standard deviation of gas mole fraction; standard deviation of gas mole fraction; CO (dry air mole fraction); CO (dry air mole fraction); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap